STUDI PERBANDINGAN KARYA STORYBOARD MAHASISWA DENGAN IMAGE GENERATED AI - Kurnia, Rudi; Ratum, Arifpermana (Prodi Teknologi Pendidikan, 2024)
This research discusses the comparison between storyboards created manually by students and those generated using an AI Image Generator. With the rapid development of artificial intelligence (AI), its usage in education, particularly in visual design, has been increasing. This study investigates whether the outputs generated by AI are comparable to manual work in terms of design principles such as emphasis, rhythm, balance, unity, as well as scale and proportion. Data were collected from the storyboard assignments of BINUS Bandung students in the